Transcriptome analysis of muscle atrophy in Leizhou black goats: identification of key genes and insights into limb-girdle muscular dystrophy - Ke Wang; Mengning Xu; Xiaotao Han; Hu Liu; Jiancheng Han; Wei Sun; Hanlin Zhou (BMC Genomics)
Abstract Background The Leizhou Black Goat (LZBG), a prominent breed in tropical China’s meat goat industry, frequently exhibits inherent muscle atrophy and malnutrition-related traits. Particularly, muscles critical for support, such as the legs, often display severe symptoms. This study aimed to investigate the differential genes and signaling pathways influencing muscle development and atrophy across various muscle locations in LZBG from a muscular atrophy-affected family. Results Differential expression analysis revealed 536 mRNAs with significant differences across three muscle groups. Marked variations in mRNA expression patterns were observed between leg and back muscles versus abdominal muscles, reflecting characteristics similar to those found in limb-girdle muscular dystrophy. The analysis identified several key differentially expressed genes implicated in muscle development and atrophy, including PITX1, COLQ, ZIC1, SBK2, and TBX1, showed Significant difference expression levels and expression patterns with normal individuals. Functional annotation and protein interaction network analysis indicated enrichment of these genes in muscle-related pathways. Protein interaction network analysis identified five key clusters related to muscle function and development. Conclusion The mRNA expression patterns of the leg and back muscles in LZBG from a muscular atrophy-affected family differed significantly from those of the abdominal muscle, displaying typical characteristics of limb-girdle muscular dystrophy. Genes such as PITX1, TBX1, SBK2, TCAP, and COLQ were identified as key regulators of muscle development and contributors to muscle atrophy. These findings enhance our understanding of the mechanisms underlying muscular atrophy in LZBGs. The identification of key genes and pathways provides valuable insights for developing future breeding strategies aimed at improving meat production efficiency.